Review of Prevention Schemes for Modification Attack in Vehicular Ad hoc Networks - Mahmood A. Al-shareeda; Mohammed Anbar; Selvakumar Manickam; Iznan H. Hasbullah (International Journal of Engineering and Management Research, 2020)
Vehicular Ad-hoc Network (VANET) technology is the basis of Intelligent Transportation System (ITS) connectivity that enables the delivery of useful information to and fro between vehicles in vehicle-to-vehicle communication mode; or between vehicle and infrastructure in vehicle-to-infrastructure mode for safety and comfort. However, due to the openness of the wireless medium used by VANET, the technology is vulnerable to security threats in both communication modes. In this study, the essential background of VANET from architectural point of view and communication types are discussed. Then, the overview of modification attack in VANET is presented. In addition, this paper thoroughly reviews the existing prevention schemes for modification attack in VANET. This review paper reveals that there is still a need for a better and more efficient preventive scheme to address the modification attack in VANET.